Q: What is 5x-3 plus 6x-4?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

The answer is 21

3x4 plus 5x3 plus x2 - 5 divided by x 2 =[(3x4) + (5x3) + (x2 - 5)]/x2 =(12 + 15 + x2 -5)/x2 =(27 - 5 + x2)/x2 =(22 + x2)/x2

3 - 2 + 6 x 4 = 25

A = 4 (7x4) + 8 = 36 (6x4) + 14 = 36

Yes 4+1=5 So 5x3=15

Related questions

The answer is 27 (6x4=24, 24+3=27)

The answer is 21

3x4 plus 5x3 plus x2 - 5 divided by x 2 =[(3x4) + (5x3) + (x2 - 5)]/x2 =(12 + 15 + x2 -5)/x2 =(27 - 5 + x2)/x2 =(22 + x2)/x2

The GCF is 5x

It is a quadratic expression

If the original is 2x + 3x2 + 6 + 5x3, you should rearrange the terms in order of exponent:5x3 + 3x2 + 2x + 6

Yes, 5x3 is the same as 5+5+5

5(x + 2y2)(x2 - 2xy2 + 4y4)

3 - 2 + 6 x 4 = 25

A = 4 (7x4) + 8 = 36 (6x4) + 14 = 36

Yes 4+1=5 So 5x3=15

6x4=24